Numerical Study of Droplet Motion inside Non-woven Fibrous Media - Seraj, Mohd.; Mohd. Yahya, Syed (CFD Letters, 2021)
The migration of liquid droplet from non-woven fibrous filter was investigated numerically using OpenFoam, an opensource CFD platform. Different droplet velocities were considered which resulted in various steady state saturation level and droplet drainage rate. In this work dependency of liquid volume fraction on velocity and time have been shown during filtration. A non-woven fibre filter having packing density 3%, with fibre diameter of 9µm and filter dimension of: 2mm(z), 0.5mm(x) & 0.5mm(y) was used. It was accomplished in this study that increasing the velocity and time, liquid volume fraction in fibrous filter get reduced. Furthermore a threshold velocity threshold of 2m/s is necessary for the motion and detachment of droplets from fibre.